Analisis Efektivitas Biaya Penggunaan Insulin Lantus dan Apidra di RSUD Dr. R. Soedjono Selong - Oktresia, Erma Ewisa; Sovia, Fitriwati; Ramadhan, Leny; Ramadani, Lalu Khilal (Universitas Hamzanwadi, 2024)
Indonesia is one of the countries with the highest number of type II diabetes mellitus patients in the world, reaching 10.7 million people. Diabetes mellitus requires long-term treatment to control patients' blood glucose levels. The types of therapy used vary, leading to differences in costs and treatment outcomes. The use of insulin is a significant issue in diabetes mellitus therapy, especially at RSUD Dr. R. Soedjono, concerning its cost-effectiveness and therapeutic efficacy. This study aims to analyze the cost-effectiveness of using Lantus and Apidra insulin therapies.This research is an observational analytic study with a cross-sectional design, and data collection was conducted retrospectively at RSUD Dr. R. Soedjono Selong. The sample selection was based on predetermined inclusion and exclusion criteria. Observations were made on the Length of Stay (LOS) and Direct Medical Cost (DMC) for each sample. Based on LOS and DMC data, the Average Cost-Effectiveness Ratio (ACER) was calculated. The results showed that the average LOS for Lantus insulin use was 4 days, while for Apidra insulin use, it was 5 days. The average DMC for Lantus insulin was Rp.2,395,734, while for Apidra insulin, it reached Rp. 2,590,218. Based on LOS and DMC data, the ACER value for Lantus insulin was Rp 598,934/day, while for Apidra insulin, it was Rp 518,043/day. The use of Apidra insulin is more cost-effective because it has a lower ACER value.